2018
DOI: 10.1142/s0192415x18500350
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenolic Compound Curcumin Conjugation with an Alkyne Moiety in the Process of Autophagy

Abstract: Curcumin is a hydrophobic polyphenol derived from turmeric: the rhizome of the herb Curcumalonga. Autophagy is an evolutionarily conserved process, in which cellular proteins and organelles are engulfed in autophagosome and then fuses with lysosome for degradation. Our previous study showed that Curcumin activates lysosome and induce autophagy through inhibition of AKT (protein kinase K, PKB)-mammalian target of rapamycin (mTOR) pathway. But whether Curucmin affects the fusion of autophagosome-lysosome is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…5) and the post-translational regulation of TFEB became the most important mechanism regulating lysosomal function in anlotinib-treated cells. On the one hand, the lower phosphorylation levels of TFEB enhanced the transcriptional activity of TFEB 16,44 ; on the other hand, the inhibition of the TFEB phosphorylation decreased its degradation and thus increased its expression levels (Fig. 5a) 45 .…”
Section: Discussionmentioning
confidence: 99%
“…5) and the post-translational regulation of TFEB became the most important mechanism regulating lysosomal function in anlotinib-treated cells. On the one hand, the lower phosphorylation levels of TFEB enhanced the transcriptional activity of TFEB 16,44 ; on the other hand, the inhibition of the TFEB phosphorylation decreased its degradation and thus increased its expression levels (Fig. 5a) 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have proposed that curcumin acts in different ways depending on its concentration: At low concentrations it functions as an antioxidant, at medium concentrations it also acts as an autophagy inductor, however it has been reported in an in vitro experiment in cancer cell that curcumin at high concentrations leads to cell death [1,4,59,60]. Although the mechanisms by which curcumin induces autophagy were initially described in cancer cells [61], they also occur in normal cells [25]. Nevertheless, their effect differ between both cell types: In normal cells, curcumin mainly induces autophagy [62] in different ways to promote cell survival (see detail in Table 2).…”
Section: Protective Effects Of Curcumin Related To Autophagy Regulmentioning
confidence: 99%
“…In addition, curcumin not only participates in the early stage of autophagy, but also in the latter stage, such as in the fusion of autophagosomes and lysosomes, as well as in the degradation of autolysosomes [25,71]. Yan et al (2018) found in mouse embryonic fibroblasts (MEF) cells exposed to curcumin, enhanced autophagic flux and lysosomal function (lysosomal acidification and cathepsin B activity) and an increased autophagosome-lysosome fusion.…”
Section: Protective Effects Of Curcumin Related To Autophagy Regulmentioning
confidence: 99%
See 2 more Smart Citations